Influence of sex and presence of cardiovascular risk factors on relations between cardiorespiratory fitness and cerebrovascular hemodynamics - Lefferts, Wesley K.; Weiner, Cynthia M.; Mascone, Sara E.; Augustine, Jacqueline A.; Heffernan, Kevin S.; Lefferts, Elizabeth C. (Journal of applied physiology (1985), 2022)
We identify beneficial associations between cardiorespiratory fitness and lower carotid stiffness and pulse pressure as potential mechanisms underlying sex-specific associations of fitness and cerebral pulsatility in females without modifiable risk factors. Greater fitness is beneficially associated with conductance, pulsatile damping, and forward wave energy among adults without risk factors; however, associations are attenuated among adults with modifiable risk factors. These data suggest sex and risk factors may alter cerebrovascular sensitivity to cardiorespiratory fitness. Cerebral hemodynamics and pulsatility are important mechanisms of cerebrovascular and brain health. Cardiorespiratory fitness may improve cerebrovascular pulsatility in healthy females, but not in males. Whether cardiovascular disease (CVD) risk factors modify sex-specific associations of fitness with cerebral hemodynamics and vascular contributors to cerebral hemodynamics is unknown. We assessed V̇o 2peak and cerebrovascular hemodynamics in 157 adults without (42 ± 13 yr, BMI 24.5 ± 2.7 kg/m 2 ), and 66 adults with modifiable CVD risk factors (54 ± 8 yr, BMI 29.9 ± 4.0 kg/m 2 ). Intracranial [middle cerebral artery (MCA) pulsatility index (PI), mean velocity, conductance, and pulsatile damping] and extracranial hemodynamics [carotid artery wave transmission/reflection, PI, pulse wave velocity (PWV)-β, and carotid-femoral PWV] were assessed via transcranial Doppler/ultrasound and tonometry. Cardiorespiratory fitness was assessed via V̇o 2peak during an incremental exercise test. Multiple regression was used to assess contributions of V̇o 2peak to cerebrovascular outcomes after adjustment for relevant covariates. V̇o 2peak was inversely associated with MCA PI among females (β = −0.39, P = 0.01) but not males (β = −0.16, P = 0.25) without CVD risk factors. V̇o 2peak was positively associated with MCA PI among females (β = 0.44, P = 0.01) and not associated in males with CVD risk factors (β = −0.06, P = 0.079). V̇o 2peak was beneficially associated with vascular contributors to cerebral hemodynamics but had sex-specific associations with carotid stiffness and pulse pressure in females without CVD risk factors only. These results suggest that sex-specific associations between fitness and cerebral pulsatility among females without CVD risk factors may relate to the differential effects of fitness on carotid stiffness and pulse pressure. In addition, the presence of modifiable CVD risk factors may influence the protective relations of fitness on cerebrovascular hemodynamics. NEW & NOTEWORTHY We identify beneficial associations between cardiorespiratory fitness and lower carotid stiffness and pulse pressure as potential mechanisms underlying sex-specific associations of fitness and cerebral pulsatility in females without modifiable risk factors. Greater fitness is beneficially associated with conductance, pulsatile damping, and forward wave energy among adults without risk factors; however, associations are attenuated among adults with modifiable risk factors. These data suggest sex and risk factors may alter cerebrovascular sensitivity to cardiorespiratory fitness.